Globalisation and innovation activity in developing countries - Tee, Chee Lip (Faculty of Economics and Administration, University of Malaya, 2018)
This paper is an empirical assessment of the impacts of globalisation on innovative activity across developing countries. The focus is on the role of trade and capital account openness. Extreme-Bound-Analysis (EBA) approach is applied to analyse data from 58 countries over the 1996-2011 period. Though globalisation leads to greater interaction between countries through trade and Foreign Direct Investment (FDI), not all of these interactions affect domestic innovation activities. The result reveal only imports of machinery and equipment promote domestic innovation activity while there is insufficient empirical evidence to suggest that this relationship exists for imports of manufactured goods and FDI inflows. This finding is consistent with the view that import is a more important channel for technology transfer than FDI.